2016
DOI: 10.1371/journal.pone.0154062
|View full text |Cite
|
Sign up to set email alerts
|

New Eocene Coleoid (Cephalopoda) Diversity from Statolith Remains: Taxonomic Assignation, Fossil Record Analysis, and New Data for Calibrating Molecular Phylogenies

Abstract: New coleoid cephalopods are described from statolith remains from the Middle Eocene (Middle Lutetian) of the Paris Basin. Fifteen fossil statoliths are identified and assigned to the Sepiidae (Sepia boletzkyi sp. nov.,? Sepia pira sp. nov.), Loliginidae (Loligo clarkei sp. nov.), and Ommastrephidae (genus indet.) families. The sediments containing these fossils indicate permanent aquatic settings in the infralittoral domain. These sediments range in age from 46 Mya to 43 Mya. Analysis of the fossil record of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…; Neige et al . ) frequently found fossilized worldwide. Conversely, coleoid soft tissues are preserved in only a handful of Mesozoic and Cenozoic Lagerstätten (Fig.…”
Section: Exceptional Preservation Of Coleoid Cephalopodsmentioning
confidence: 99%
“…; Neige et al . ) frequently found fossilized worldwide. Conversely, coleoid soft tissues are preserved in only a handful of Mesozoic and Cenozoic Lagerstätten (Fig.…”
Section: Exceptional Preservation Of Coleoid Cephalopodsmentioning
confidence: 99%
“…Belosaepia sepioides was reported from offshore shale of the Ilaro Formation (Lutetian) overlying the Paleocene of south-western Nigeria from a diverse fauna lacking seagrass indicators (PDB 77257). Neige et al (2016) recorded coleoid statoliths from the middle Lutetian (middle Eocene) of Thiverval-Grignon (Paris Basin, France). They erected two new species, Sepia boletzkyi and ?Sepia pira for statoliths from beds 3b (clayey limestone) and 4a (glauconitic, calcareous sand) at the Thiverval-Grignon section.…”
Section: Late Cretaceous-eocenementioning
confidence: 99%
“…have indicated that buoyancy mechanisms may limit cephalopod soft tissue preservation and may have implications for lack of fossilised cuttlefish. The record of Sepia statoliths from the middle Lutetian (middle Eocene) of Thiverval-Grignon (Paris Basin, France) (Neige et al, 2016) infers that the cuttlebone has gone and that soft parts have disintegrated or been eaten leaving only the aragonitic statoliths to be preserved.…”
Section: Taphonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the inventory is highly thorough, new species may still be found. In 2016, statoliths of Sepia (cuttlefish) and Loligo (squid) found in the fossil site allowed to identify three new species (Neige et al, 2016). These are the oldest fossils of cuttlefish and squid found in the world.…”
Section: Paleontological Interestmentioning
confidence: 99%